Recurrent “transient ischemic attacks” caused by pulmonary arteriovenous malformation - Jorrit B.A. Welling; Mascha Schuurmans; T. David Koster (Respiratory Medicine Case Reports)
Pulmonary arteriovenous malformations (PAVMs) are abnormal, direct connections between a pulmonary artery and pulmonary vein that can lead to severe neurologic complications including ischemic stroke. This case report describes a 39-year-old woman who presented with recurrent transient ischemic attacks (TIAs). Extensive clinical evaluation revealed PAVM as the underlying cause. Following successful embolization of the PAVM, the patient did not experience further TIAs. This case highlights the importance of considering PAVMs in the differential diagnosis of recurrent TIAs, particularly in patients without traditional risk factors for cerebrovascular events.